In situ formation of gold nanoparticles@supramolecular hydrogels with ultra-fast catalytic reduction of dyes and excellent anti-bacterial properties. (23rd March 2023) - Wang, Xiao-Juan; Zhang, Lang; Wei, Chuan-Wan; Gao, Shu-Qin; Luo, Wei; Lin, Ying-Wu
Abstract : 2-QY-Au NPs@metallohydrogel could catalyze and degrade a variety of organic dyes with an excellent catalytic activity and presented good biocompatibility and antibacterial activity. Abstract : In this study, we have synthesized a facile tyrosine derivative based compound (2-QY), which can act both as a gelator and a reducing agent. 2-QY can assemble to form a functional metallohydrogel (2-QY-Au) in the presence of HAuCl4 under mild conditions (room temperature, aqueous solution, and simple sonication treatment). Au nanoparticles (Au NPs) can be in situ formed and dispersed uniformly in the gel system, which did not require an external reducing agent and a stabilizing agent. The obtained 2-QY-Au NP@metallohydrogel can be used as a catalyst to degrade a variety of dyes, such as methyl orange, methyl green, reactive black 5, reactive orange 16, and p -nitrophenol. In particular, it exhibits excellent catalytic activity towards degradation of methylene blue in the presence of NaBH4, with a k app value (13.23 ± 0.21 s −1 ) higher than those of most of the reported catalysts in the literature. Moreover, 2-QY-Au NPs have good biocompatibility and exhibit antibacterial activity against E. coli and B. subtilis . Therefore, the 2-QY-Au NP@metallohydrogel could be used as an effective catalyst for the degradation of pollution containing organic dyes, as well as for potential applications in the biomedical field.